Small firms' formalization: The stick treatment - Giacomo De Giorgi; Matthew Ploenzke; Aminur Rahman (Federal Reserve Bank of New York, 2015)
Firm informality is pervasive throughout the developing world, and Bangladesh is no exception. The informal status of many firms substantially reduces the tax basis and therefore affects the provision of public goods. The literature on encouraging formalization has focused predominantly on reducing the direct costs of formalization and has found negligible effects from such policies. In this paper, we focus on a stick intervention, which, to the best of our knowledge, is the first in a developing-country setting to deal with the most direct and dominant form of informality: the lack of registration with the tax authority and direct link to the country's potential revenue base and thus public goods provision. We implement an experiment in which firms are visited by representatives who deliver an official letter from the Bangladesh National Tax Authority stating that the firm is not registered and threatening punishment if it fails to register. We find that the intervention increases the rate of registration among treated firms, while firms located in the same market but not treated do not seem to respond significantly. We also find that only larger-revenue firms at the baseline respond to the threat and register. Our findings have at least two important policy implications: 1) the enforcement angle, which could be an important tool to encourage formalization; and 2) targeting of government resources for formalization to the high-end informal firms. The effects are generally small in level, leaving open the question of why many firms still do not register.
Keywords: O1; 330; firms; informality; development